Hypoxia recruits intrapulmonary arteriovenous pathways in intact rats but not isolated rat lungs - Bates, Melissa L. (American Physiological Society, 2012)
Intrapulmonary arteriovenous anastomoses (IPAVS) directly connect the arterial and venous circulations in the lung, bypassing the capillary network. Here, we used solid, latex microspheres and isolated rat lung and intact, spontaneously breathing rat models to test the hypothesis that IPAVS are recruited by alveolar hypoxia. We found that hypoxia recruits IPAVS in the intact rat, but not the isolated lung. IPAVS are at least 70 μm in the rat and, interestingly, appear to be recruited when the mixed venous Po(2) falls below 22 mmHg. These data provide evidence that large-diameter, direct arteriovenous connections exist in the lung and are recruitable by hypoxia in the intact animal.